(untitled) (MODERN CONSTRUCTION AND ARCHITECTURE, 2023)
The paper describes the use of various types of mechanical filter models, which are used for the analysis of the processes of formation and compaction of the construction/concrete mixtures of building/concrete mixtures by means of vibrating fields. The values of resonant frequencies and equivalent masses for different resonators modeling the propagation in the latter of vibrating-wave formations have been established. The analysis of the influence of a vibrating field on the processes of formation and compaction of concrete/concrete mixtures in this study is based on the methods of mathematical physics, classical variation calculus, physics of oscillations and waves and methodology of solution of ordinary differential equations and partial differential equations. The conditions and main integral characteristics of resonance phenomena, the possibility of occurrence of which is conditioned by: 1) the geometry of the initial boundary-edge problem (it is The so-called "geometric resonances" of the considered system with distributed parameters simulating the mixture to be processed); 2) the working rheological model of the mixture involved in the study (these are the so-called "rheological resonances"). The approach developed and scientifically substantiated in this work allows us to establish the main parameters and opportunities for the use of energy-saving modes of operation of vibration systems intended for the formation and vibration compaction of the above mixtures. The results obtained in the work The results obtained can be further used to clarify and Improvement of existing engineering methods of calculation of vibration systems for the formation and compaction of concrete/concrete mixtures in order to optimize the operating modes of their functioning both at the design stage and in the modes of real operation.